Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/01916122.2010.545515
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of non-pollen palynomorphs in palaeoecology with examples from Australia

Abstract: Records of the past climate and vegetation of Australia are frequently constructed using data generated from the analysis of pollen and pteridophyte spores alone, or in association with sedimentology. We demonstrate that the organic residue prepared for pollen analysis yields other organic-walled microfossils that can be used to provide additional and independent palaeoenvironmental information. These non-pollen palynomorphs (NPP) include microscopic remains of algae, cyanobacteria, fungi, insects, other inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 112 publications
1
31
0
5
Order By: Relevance
“…They are ascospores with a sigmoid germinal aperture extending the entire length of the cell. Cells are 12–28 μm × 9–15 μm and are present as two types; end cells show one flattened and one round end, middle cells show two flattened ends53 (Supplementary Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…They are ascospores with a sigmoid germinal aperture extending the entire length of the cell. Cells are 12–28 μm × 9–15 μm and are present as two types; end cells show one flattened and one round end, middle cells show two flattened ends53 (Supplementary Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Many authors mention that the fungi occur in significant quantities and diversities in peat deposits (Schof 1946;Van Geel 1978, Cook et al 2011Hower et al 2013;O'Keefe et al 2013). Although A. capitata is more frequent in coal seams in the Cañad on Asfalto Formation, it is also present in samples from other facies, such as proximal prodelta sediments (e.g., MPEF-PALIN123, Olivera et al 2013).…”
mentioning
confidence: 95%
“…In this study, Breil (1970) found that these two genera were strictly found in association with moist rotten stumps or logs, on moist soil, in moist quartzitic sand (but rarely on limestone), in ditches, along streams and riverbanks and commonly on wet floodplains and in freshwater swamps. While conducting a palynological analysis of non-pollen palynomorphs of Australia, Cook et al (2011) noted that Anthoceros spores are generally found in moist shady environments during warm and wet time intervals conducive to swamp development.…”
Section: Habitat Preferencementioning
confidence: 99%